P59-T The utility of sural NCS in differentiation of AIDP, CIDP and CMT1A. Issue 7 (July 2019) - Soerensen, Daniel; Fuglsang-Frederiksen, Anders; Vaeth, Signe; Markvardsen, Lars Kjøbstad; Harbo, Thomas; Andersen, Henning; Tankisi, Hatice
Abstract : Objective: Nerve conduction studies (NCS) are mainstay in diagnosis and classification of polyneuropathies as demyelinating or axonal. However, detection of demyelination and differentiation of hereditary and inflammatory polyneuropathies are mainly based on motor NCS. The aim of this study was to examine the utility of sural NCS in differentiation of the three most common demyelinating polyneuropathies; Acute Inflammatory Demyelinating Polyneuropathy (AIDP), Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) and Charcot-Marie-Tooth-Disease type 1A (CMT1A). Methods: Fifty-eight patients (mean age: 50.90 ± 14.29) were included. Of these, 16 had AIDP, 19 CIDP and 23 CMT1A with PMP22 duplication. Sural nerve was examined with surface electrodes (13 patients) or near-nerve needle technique (45 patients). Results were compared to laboratory controls. The pathophysiological state of the sural nerve was classified as normal, axonal loss or demyelinating according to ESTEEM criteria (Tankisi et al., 2005). Results: Of 16 AIDP patients, 10 had normal sural NCS, 2 demyelination and 4 axonal loss. CIDP patients had either axonal (14) or normal (5) sural NCS whereas all CMT1A patients showed demyelination. Sural sensory CV could distinguish all patients with CMT1A (CV < 30 m/s) from CIDP (CV > 35 m/s). AIDP and CIDP patients had significantly higher CV (42.6m/s ± 5.6 and 46.5m/s ± 8.1, respectively) than CMT1A (22.5m/s ± 5.3)( p < 0.001). Sensory amplitudes were higher in AIDP (11.2 μ V ± 9.4) than CIDP (4.2 μ V ± 4.9) and CMT1A (3.0 μ V ± 4.5)( p < 0.05). Conclusion: Sural NCS may contribute to differentiation of AIDP, CIDP and CMT1A. Demyelination is characteristic for CMT1A and axonal loss is mostly seen in CIDP whereas in AIDP sural nerve is often normal.